Challenges and opportunities in 3D laser printing based on (1+1)-photon absorption - Hahn, Vincent; Bojanowski, N. Maximilian; Rietz, Pascal; Feist, Florian; Kozlowska, Mariana; Wenzel, Wolfgang; Blasco, Eva; Bräse, Stefan; Barner-Kowollik, Christopher; Wegener, Martin (ACS photonics, 2023)
Most light-based 3D printing methods rely on optical or chemical nonlinearities to spatially confine the polymerization reaction. In 3D micro- and nanoprinting, this nonlinearity can be provided by two-photon absorption, which describes the simultaneous absorption of two photons. To achieve comparable absorption cross sections for two-photon as in one-photon absorption, short and intense laser pulses with intensities in the range of 1 TW/cm2 are typically required. Herein, we review three emerging excitation processes that provide a quadratic nonlinearity versus intensity without relying on two-photon absorption: upconversion luminescence, two-step absorption, and triplet-triplet annihilation. We term these “(1 + 1)-photon absorption”. Such processes allow for using continuous-wave lasers at much lower peak laser powers and at much lower cost than those typical for two-photon absorption. We review recent progress, describe current challenges, and outline future perspectives.
Online veröffentlicht 14 Dezember 2022
Gesehen am 20.03.2023